IMPLEMENTASI DAN EVALUASI SISTEM ENTERPRISE RESOURCE PLANNING (ERP) MODUL AKUNTANSI ODOO UNTUK MANAJERIAL AKUNTANSI PADA INDUSTRI PELUMAS PT. PETRONAS LUBRICANTS INTERNATIONAL INDONESIA DENGAN COMMERCIAL PACKAGE - Unik Sekar Rera; Bani Saad (Journal of Accounting, Management and Islamic Economics, 2025)
This research addresses the pressing need for PT. Petronas Lubricants International Indonesia (PLII) to enhance the efficacy and efficiency of their accounting management amidst heightened global competition. Employing a descriptive qualitative method with a case study approach, the study involves data acquisition through interviews, observations, and document analysis. The findings highlight a commendable success rate of 100% in implementing the Odoo Enterprise Resource Planning (ERP) system. However, the adherence to PSAK No.1 standards for the Profit and Loss Statement (PL) registers at 60%, encompassing only three of the mandated five accounts. Nevertheless, the Balance Sheet and Cash Flow Statement have fully complied with PSAK No.1 requirements. In essence, this research significantly contributes to augmenting the quality and efficiency of accounting management at PLII. It underscores the imperative for continual evaluation and enhancement of the Odoo ERP system to fortify future business expansion and sustainability.